Quinoxaline-2, 3-Dione: Chemical Structure, Synthetic Strategies, Structure–Activity Relationship, Reactivity, and Pharmacological Activities - V Vani; Gopal Lakshmi; Shajahan Rushda; B Theertha; I Thoufeek (Asian Journal of Pharmaceutical Research and Development, 2026)
Quinoxaline‑2,3‑dione, a bicyclic heteroaromatic scaffold, has emerged as a versatile pharmacophore with wide‑ranging biological activities. Its fused benzene–pyrazine ring system bearing adjacent carbonyl groups at positions 2 and 3 provides a reactive framework for diverse synthetic modifications. Several methodologies, including solvent‑free grinding, acid‑catalyzed reflux, thermal conditions, and microwave irradiation, have been developed for efficient synthesis of quinoxaline‑2,3‑dione derivatives, highlighting their accessibility and reproducibility. Structure–activity relationship studies reveal that substitution at positions C‑6 and C‑7 with nitro groups enhances antibacterial and anti‑inflammatory properties, while reduction to amines or incorporation of p‑fluorophenyl and dimethylamino groups confers potent analgesic activity. The compound’s reactivity encompasses N‑alkylation, nitration, chlorination, and nucleophilic substitution, enabling the generation of structurally diverse analogues. Pharmacological investigations demonstrate promising anticancer potential, with derivatives showing cytotoxicity against lung and cervical cancer cell lines, alongside neuroprotective effects in demyelination models. Antibacterial activity against Gram‑positive and Gram‑negative pathogens further underscores its therapeutic relevance. Additionally, receptor antagonism studies highlight its role in modulating AMPA and GlyN receptors, supporting neuroprotective applications. Collectively, quinoxaline‑2,3‑dione represents a privileged scaffold for drug discovery, with synthetic versatility, favorable pharmacokinetics, and broad pharmacological potential across oncology, neurology, and infectious disease research.